2008
DOI: 10.1038/gt.2008.30
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein inhibitors increase the efficacy of measles virotherapy

Abstract: Oncolytic measles virus strains have activity against multiple tumor types and are currently in phase I clinical testing. Induction of the heat shock protein 70 (HSP70) constitutes one of the earliest changes in cellular gene expression following infection with RNA viruses including measles virus, and HSP70 upregulation induced by heat shock has been shown to result in increased measles virus cytotoxicity. HSP90 inhibitors such as geldanamycin (GA) or 17-allylaminogeldanamycin result in pharmacologic upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Moreover, independent of decreased protection in homeostasis of [Ca 2+ ] i , reduced Hsp70 could also increase calcium sensitivity in smooth muscle cells. And reduced Hsp70 could lead to the Ca 2+ sensitivity and smooth muscle contraction increase through a small GTPase protein, RhoA [29][30][31]. Furthermore, some studies demonstrated that overexpression of Hsp70 protected paxillin, a focal adhesion-associated adapter protein, and the dynamic assembly and disassembly of focal adhesions plays a central role in cell mobility [32].…”
Section: Months) With 1-month Exposure There Is Slight Infiltrationmentioning
confidence: 97%
“…Moreover, independent of decreased protection in homeostasis of [Ca 2+ ] i , reduced Hsp70 could also increase calcium sensitivity in smooth muscle cells. And reduced Hsp70 could lead to the Ca 2+ sensitivity and smooth muscle contraction increase through a small GTPase protein, RhoA [29][30][31]. Furthermore, some studies demonstrated that overexpression of Hsp70 protected paxillin, a focal adhesion-associated adapter protein, and the dynamic assembly and disassembly of focal adhesions plays a central role in cell mobility [32].…”
Section: Months) With 1-month Exposure There Is Slight Infiltrationmentioning
confidence: 97%
“…The expression of Helicobacter pylori neutrophil-activating protein (NAP), by attenuated MV has also been shown to induce a potent anti-tumour immune response in lung and intrapleural metastatic breast cancer xenograft models via stimulating the release of proinflammatory cytokines [77]. MV has also been engineered to code for other immune-stimulating transgenes including interleukin (IL-13) [78] and heat shock protein inhibitors [79]. …”
Section: Engineering Oncolytic Measles Virusmentioning
confidence: 99%
“…These include: adult acute lymphoblastic leukemia and chronic lymphocytic leukemia [58,59], adult T cell leukemia/lymphoma [60], atypical teratoid rhabdoid tumor [61], breast cancer [44,62], cholangiocarcinoma [63], colorectal cancer [64], cutaneous T cell lymphoma [65], gliomas [66], head and neck squamous cell cancer [67], hepatoblastoma [68], hepatocellular cancer [51], lung cancer [64,69,70], malignant peripheral nerve sheath tumor [71], mantle cell lymphoma [72], medulloblastoma [53,73,74], melanoma [75,76], mesothelioma [77,78], multiple myeloma [47,79], non-Hodgkin’s lymphoma [80], osteosarcoma [81], ovarian cancer [52,82,83], pancreatic cancer [49,50,84], prostate cancer [45,85], renal cell carcinoma [86], rhabdomyosarcoma [87], and splenic marginal zone lymphoma [88]. …”
Section: Improving the Oncolytic Efficacy And Safety Of MV Strainsmentioning
confidence: 99%
“…An enhancement of the MV cytopathic effect was seen when the heat shock protein 90 inhibitor geldanamycin, was combined with the oncolytic MV-CEA strain in breast, ovarian and rhabdomyosarcoma cell lines with significant increase in apoptosis mediated via the extrinsic caspase pathway [87]. Inhibition of Rho-associated coiled-coil-forming kinase in combination with MV infection similarly enhanced the cytopathic effect in breast, glioblastoma and prostate cancer cell lines through disruption of the cytoskeleton and increased fusogenicity [123].…”
Section: Improving the Oncolytic Efficacy And Safety Of MV Strainsmentioning
confidence: 99%